GDPR Data Interoperability Model - PANDIT, HARSHVARDHAN JITENDRA; Lewis, David; O'Sullivan, Declan (My University, 2018)
Laws such as the General Data Protection Regulation (GDPR) specify information to be shared, provided, or communicated between entities as part of its operation and compliance. Its compliance additionally requires provision of information between the entities to follow the requirements and procedures outlined in the text. GDPR also provides explicit cases of data interoperability such as that provided by the right of a data subject to move their personal data between different data controllers. In this paper, we explore the interoperability of information between the various entities mentioned within GDPR. We identify various procedures outlined for information flows which also contain explicit requirements such as presence of structured data or specific data formats being used and provide a discussion of existing standards by evaluating the state of the art with respect to the standards provided by the World Wide Web Consortium (W3C) for representing information.
23rd EURAS Annual Standardisation Conference
Keywords: GDPR; Interoperability; Data protection; Data sharing